The role of green tea intake in thromboprophylaxis of venous thromboembolism in patients with cancer - Yao, Qihuan; Qiao, Hongwei; Cheng, Yi; Du, He; Zhang, Yanbin; Luo, Yong; Wang, Hongwei; Liu, Song; Xu, Mei; Xiong, Wei (Frontiers in Nutrition, 2024)
Background Green tea intake has been reported to improve the outcomes of patients with cardiovascular diseases or cancer. It may have certain role in the development of venous thromboembolism (VTE) among cancer patients. The current study was to address this issue which has been understudied. Methods We launched a retrospective study to explore the role of green tea intake in cancer patients. Patients with and without green tea intake were collected in a 1:1 ratio by using propensity scoring match. The primary and secondary outcomes were VTE development and mortality one year after cancer diagnosis, respectively. Results The cancer patients with green tea intake (n=425) had less VTE development (10 [2.4%] vs 23 [5.4%], P=0.021), VTE-related death (7 [1.6%] vs 18 [4.2%], P=0.026), and fatal pulmonary embolism (PE) (3 [0.7%] vs 12 [2.8%], P=0.019), compared with those without green tea intake (n=425). No green tea intake was correlated with an increase of VTE development (multivariate hazard ratio [HR]1.758 [1.476-2.040], P<0.001) and VTE-related mortality (HR1.618 [1.242-1.994], P=0.001), compared with green tea intake. Patients with green tea intake less than 525 mL per day had more VTE development (area under the curve [AUC] 0.888 [0.829-0.947], P<0.001; HR1.737 [1.286-2.188], P=0.001) and VTE-related mortality (AUC0.887 [0.819-0.954], P<0.001; HR1.561 [1.232-1.890], P=0.016) than those with green tea intake more than 525 mL per day. Green tea intake caused a decrease of platelet (P<0.001) instead of D-dimer (P=0.297). The all-cause mortality rates were similar between green tea (39 [9.2%]) and non green tea(48 [11.3%]) groups (P=0.308), whereas the VTE-related mortality rate in the green tea group (7 [1.6%]) was lower than that of the non green tea group (18 [4.2%]) (P=0.026). The incidence of adverse events were similar between the green tea and non green tea groups. Conclusions In conclusion, the current study suggests that green tea intake reduces VTE development and VTE-related mortality in cancer patients, most likely through antiplatelet mechanism. Drinking green tea has the efficacy of thromboprophylaxis for cancer patients.